Tranformation The Talaqqī System of Reciting The Qur'an Using Artificial Intelligence - Nurul Istiqomah; Yayuk Whindari; Sheila Kusuma Wardani Amnesti (UIN Sunan Gunung Djati Bandung, 2024)
Background: The talaqqī system in Qur’anic education traditionally emphasizes direct interaction between teacher and student to ensure authenticity of recitation and the transmission of spiritual values. However, the advancement of digital technology—particularly the use of artificial intelligence (AI)—has introduced new models in Qur’anic pedagogy. One example is the Qara’a application, which offers a self-directed learning method without the physical presence of a teacher. Purpose: This study aims to analyze the transformation of the talaqqī system into a digital format through the Qara’a application and to evaluate the accuracy of its Qur’anic recitation assessment system. Methodology: This study employs a descriptive qualitative approach with structured digital observation of the Qara’a application. The researcher directly engaged with the app to document its navigation flow, AI features, and learning system. Data were collected through screenshots and field notes, and analyzed thematically through the stages of data reduction, categorization, interpretation, and conclusion drawing. Findings: The results show that in the Qara’a system, the teacher’s role is replaced by a machine that provides sample recitations, which are then imitated by the learner through voice recordings. The learning materials are structured in stages—covering writing, recitation, and a combination of both—and users cannot proceed to the next level without completing the current one. While the app offers flexibility in terms of time and place, its AI-based assessment focuses solely on makhraj (articulation point) per letter and does not account for technical issues (such as voice clarity and network stability) or the psychological state of the learner. Research Implication: These findings reveal a shift in the value system of talaqqī, from one rooted in spiritual relationships to an automated evaluative system, affecting both the meaning of authority and the quality of assessment in Qur’anic learning. Contribution: This study offers a new contribution to the field of digital Qur’anic education by presenting a critical analysis of AI integration in Islamic pedagogy. Its focus on the transformation of talaqqī and the evaluation mechanism of the Qara’a application represents a dimension that has not been widely explored in previous studies.